Co-crystallisation of 2,2′-dithiodibenzoic acid with the isomeric n-pyridinealdazines, n = 2, 3 and 4: Supramolecular polymers and the influence of steric factors upon aggregation patterns - Broker, G.A. (2014)
10.1039/b800797g